Arthroscopic-assisted inflatable bone tamp reduction for treatment of posterolateral tibial plateau fractures. Issue 11 (November 2018) - Liang, Junbo; Zhang, Qingguo; Liu, Peihong; Wang, Bin; Zhou, Xiaobo; Chen, Guofu; Zhang, Chuanyi; Xu, Youjia
Highlights: First, the study described the utilization of arthroscopy in the reduction of posterolateral tibal plateau fractures. It satisfies the minimal invasive concept which prevents from excessive iatrogenic injuries during surgeries. Second, the inflatable bone tamp is first used in treatment of posterolateral tibial plateau fractures. The technique is proved to be minimally invasive, safe, accurate and effective, even though the study is not completely randomized control. This study provided a novel technique for performing the reduction of depressed and split-depressed pasterolateral tibial plateau fractures. It offers distinct advantages of clear vision, accurate reduction, minimally invasive and preservation of the soft tissue envelope. In addition, the expanded cavity below the articular surface allows for the insertion of a larger amount of bone void filler that should be more stable structurally and rigid biomechanically. Arthroscopic-assisted inflatable bone tamp reduction may be an effective method for the surgical treatment of posterolateral tibial plateau fractures. Abstract: Aim: Our study aimed to assess the safety and efficacy of an innovative arthroscopic-assisted inflatable tamp reduction technique for the treatment of posterolateral tibial plateau fractures. Patients and methods: Twenty-six patients with posterolateral tibial plateau fractures were treated with arthroscopy through inflation reduction technique were enrolled. Arthroscopy was used to observe the reduction of articular surface to avoid over-reduction or de-reduction. An arthroscopic assessment of anatomic joint reduction completed the procedure. Inflatable bone tamp was used to reduce the fractures and calcium phosphate cement was used as bone substitute to augment the repairs. Results: Under arthroscopy, the reduction was observed to be excellent without any residual deformity in all the cases. Cement overflow into the soft tissues or the knee joint was not observed. During the follow-up period, no obvious articular surface subsidence (>5 mm) was observed and no evidence of posttraumatic osteoarthritis could be detected. Radiographs under full weight bearing revealed neither loss of reduction nor any valgus deviation. Three months after surgery, the graft was almost completely replaced by new bone. The functional evaluation following the Rasmussen score yielded excellent results. Conclusions: This study provided a novel technique for the reduction of depressed and split-depressed pasterolateral tibial plateau fractures. Arthroscopic-assisted inflatable bone tamp reduction is an effective method for the treatment of posterolateral tibial plateau fractures.